THE ROLE OF INFORMATION TECHNOLOGY IN MEDICINE: TRANSFORMING HEALTHCARE DELIVERY AND MANAGEMENT (Modern education and development, 2025)
In the 21st century, Information Technology (IT) has become a cornerstone of modern medicine. Its integration into healthcare has brought about revolutionary changes, enhancing patient care, improving clinical outcomes, and optimizing healthcare management. This article explores the various applications of IT in medicine, including electronic health records (EHRs), telemedicine, medical imaging, artificial intelligence (AI), and data analytics. The paper discusses the benefits, challenges, and future prospects of IT in the healthcare sector.